WOUND INFECTIONS IN PATIENTS WITH UROLOGICAL CANCER - I. N. Petukhova; Z. V. Grigoryevskaya; N. V. Dmitrieva (Сибирский онкологический журнал)
This review of the literature is devoted to the analysis of wound infections in patients with urological cancer. Compared to data on urological infections, a few reports on wound complications have been available. The information on the resistance of pathogens is particularly relevant, since it significantly affects the choice and adequacy of antibiotic therapy, allowing the infection to be overcome as quickly as possible.